The Growing Importance of CNVs: New Insights for Detection and Clinical Interpretation - Valsesia, Armand; Mace, Aurélien; Jacquemont, Sébastien; Beckmann, Jacques S.; Kutalik, Zoltán (Frontiers in Genetics, 2013)
Differences between genomes can be due to single nucleotide variants, translocations, inversions and copy number variants (CNVs, gain or loss of DNA). The latter can range from sub-microscopic events to complete chromosomal aneuploidies. Small CNVs are often benign but those larger than 500kb are strongly associated with morbid consequences such as developmental disorders and cancer. Detecting CNVs within and between populations is essential to better understand the plasticity of our genome and to elucidate its possible contribution to disease. Hence there is a need for better-tailored and more robust tools for the detection and genome-wide analyses of CNVs. While a link between a given CNV and a disease may have often been established, the relative CNV contribution to disease progression and impact on drug response is not necessarily understood. In this review we discuss the progress, challenges and limitations that occur at different stages of CNV analysis from the detection (using DNA microarrays and Next Generation Sequencing) and identification of recurrent CNVs to the association with phenotypes. We emphasise the importance of germline CNVs and propose strategies to aid clinicians to better interpret structural variations and assess their clinical implications.